APPLICATION OF FAST-TRACK LEGISLATION METHOD IN PRESIDENTIAL SYSTEM OF GOVERNMENT IN INDONESIA - Wand Mei Herry Susilowati (Cepalo)
The amendment of the 1945 Constitution is strengthening the Indonesian presidential system of government by granting the President the authority to issue Government Regulations in Lieu of Laws (Perppu) in response to urgent situations. Additionally, the President and DPR (House of Representatives) jointly discussed and ratified draft laws, providing the President legislative authority in normal, abnormal, or urgent circumstances. When a president with majority parliamentary support holds legislative power, it suggests that parliament has delegated the legislative power to the executive. The current phenomenon shows numerous Perppu issued that may deviate from the provisions of Article 22 paragraph (1) of the 1945 Constitution and Constitutional Court Decision No.138/PUU-VII/2009 giving juridical interpretation to “compelling urgency”. Simultaneously, there is a rise in flash legislation that seems “rushed” in the formation aiming to meet legislative targets. For instance, the Job Creation Bill in Indonesia took 167 days to be enacted despite consolidating 79 laws into a single policy. In Indonesia's presidential system of government, the DPR holds the power to form laws as observed in Article 20 of the 1945 Constitution. This suggests that the fast-track legislation method should strengthen the presidential system, especially in legislation. However, numerous Perppu continue to be issued representing executive authority in legislation. The fast-track method lacks regulation in Indonesian positive law due to the following questions arising, (1) What is the relationship between the fast-track legislation method and Indonesia's presidential system? and (2) How should the fast-track legislation method be ideally applied in law formation according to the 1945 Constitution amendments? Therefore, this research aimed to offer a concept for applying the fast-track legislation method in Indonesia’s presidential system of government according to the 1945 Constitution. A qualitative method was adopted in the research using statutory, conceptual, comparative, and case methodologies. The statutory method included reviewing and identifying laws as well as regulations related to the problem’s formulation. The conceptual method deviated from the doctrine or views in law, particularly constitutional law relating to the formation of laws and regulations using the fast-track legislation method in Indonesia’s presidential system of government. The results found that applying the fast-track legislation method in the Indonesian presidential system to hasten the formation of laws could balance the legislative authority of the President in issuing Perppu, thereby reducing the issuance. Additionally, the fast-track legislation method would further strengthen and purify the presidential system with checks and balances between the executive and legislative institutions. In this method, the procedures would remain consistent with normal law formation provisions, ensuring public participation, information disclosure, and transparency. Therefore, the research recommended that the fast-track method be used for law formation with strict regulations in the presidential system. This should also adhere to guidelines for creating good laws and regulations and providing ample space for public participation in every step while upholding democratic principles.